Streamology Contemporary Hawrami literature; poem - Farshid Rostami; Kourosh Amini (پژوهشنامه ادبیات کردی)
Some historians of Kurdish literature believe that the oldest poem written in Hawrami is the text of "Hormozgan Roman, Ateran Kozhan". Hawrami poetry has been written for at least fourteen centuries without interruption, even after the advent of Islam. In addition to the ten-syllable masnavi metre, classical Hawrami poetry in the period of Sheikh Shahabuddin Kakuzekeriai and Seidi gradually incorporated prosodic poetry into the language. After Mawlavi, classical poetry as a whole changed more in form and content. After the 1970s, Hawrami poetry experienced its first changes to free itself from the constraints of metre and break the classical structure. In this research, an attempt has been made to analyze half a century of renaissance in Hawrami poetry. The obtained results indicate that in the 1970s, the flow of new poetry began in a free form, under the influence of Sorani Kurdish new poetry. Additionally, classical poetry, in the form of 5+5 syllabic metre and prosodic metre, has undergone significant changes in content. Among the prominent characteristics of Hawrami's contemporary poetry movement, we can mention the breadth of content, the representation of experience, the presence of women poets, and the emergence of literary criticism alongside this movement.